Economic burden associated with chronic constipation in Sweden: a retrospective cohort study - Bruce Wirta S; Hodgkins P; Joseph A (Dove Medical Press, 2014)
Sara Bruce Wirta,1 Paul Hodgkins,2 Alain Joseph3 1IMS Health, Stockholm, Sweden; 2Shire, Wayne, PA, USA; 3Shire, Eysins, Switzerland Background: Chronic constipation is a common condition, but few studies have assessed its cost and impact on resource use. The purpose of this cohort study was to assess the health care utilization and costs of chronic constipation in a Swedish population using health care claims data. Methods: Data were compiled on health care costs, drug costs, and mortality for Västra Götaland, Sweden (2005–2009). These data were used to identify patients aged 18 years or older with chronic constipation, defined as: at least two health care contacts with a primary diagnosis of constipation within 12 months or at least one care contact with a primary diagnosis of constipation and two dispatches of laxatives 6 months before and 12 months after the index date. Patients with irritable bowel syndrome or taking opioids, both of which can cause constipation, were excluded. Costs, resource use, comorbidities, and laxative use were assessed during a 12-month follow-up period. Results: In total, 4,043 patients with chronic constipation were identified. They had a mean (SD) age of 67±18 years. Mortality was 7% during the 12-month follow-up period and the most common comorbidity was hypertension (22%). In the 12-month follow-up period, patients with chronic constipation had a mean (SD) of 2.3±7.5 constipation-related health care contacts and a mean (SD) of 15.2±19.5 other health care contacts. Annual costs, adjusted for sex, age group, mortality, and comorbidities, were €5,388, of which €951 were for constipation-related care. Conclusion: Patients with chronic constipation constituted an elderly population with a high disease burden in Sweden between 2005 and 2009. Mean annual constipation-related health care costs, adjusted for potentially confounding factors, were €951 per patient. Keywords: cohort study, chronic constipation, costs, Sweden